The role of rural libraries in preserving the indigenous knowledge of rural residents: The case of South Khorasan Province. Issue 3 (9th July 2018) - Forutnani, Solmaz; Nowkarizi, Mohsen; Kiani, Mohammad Reza; Mokhtari Aski, Hamid Reza
Abstract : Purpose: The purpose of this paper is to investigate the potential or actual role of rural libraries in preserving indigenous knowledge (IK) of the rural residents in South Khorasan province. Design/methodology/approach: The study, based on a qualitative research, was carried out by employing the grounded theory method. Data were collected by semi-structured interviews from the research sample population which included 20 rural males, 10 rural females, 8 librarians and 3 well-informed regional IK specialists. The validity of the research was confirmed by peer evaluation, compounded by detailed thorough explanations and external reviewers' reaffirmations. Findings: The rural residents of the South Khorasan villages across the province, after having realized the vitality of carrying out this project, were fully motivated and cooperative to provide indigenous knowledge. On the basis of the results from the rural libraries, due to being the solitary knowledge center in the area, these libraries could actively participate in preserving the knowledge and contribute toward the documentation of the indigenous knowledge. This required motivating librarians and increasing their professional, technical, research and verbal skills. The results of the study indicated that, even if the rural libraries of the South Khorasan province did not participate in documentation, preservation, and promotion of the IK and opt for the present form of non-participation, due to their inherent nature, they could become a focal point and play an indispensable role in achieving the objectives by aiding and leading the process at country level and become a focal point for the new generations of rural inhabitants to enlighten themselves and become fully aware of the value of the ancestral knowledge. Originality/value: Hitherto, none of the researchers in Iran has covered the role of the libraries in general and rural libraries in particular in preserving the indigenous knowledge.